2018
DOI: 10.1159/000489830
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Infection: A General Overview

Abstract: After initial infection, the immune response that serves to restrict the invading pathogen needs to be tightly calibrated in order to avoid collateral immunopathological damage. This calibration is performed by specialized suppressor mechanisms, which are capable of dampening overwhelming or unremitting inflammation in order to prevent tissue damage. Myeloid-derived suppressor cells (MDSC) are emerging as key players in counter-balancing inflammatory responses and pathogenesis during infection. However, some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 43 publications
7
94
0
Order By: Relevance
“…Instead, during histotropic phase of infection, we saw increased numbers of CD11b+Gr‐1+ cells in peritoneal fluid. Peritoneal cavity was shown to be an important trafficking site for intestinal immunity; therefore, parasite‐induced cells could migrate through the peritoneum to other lymphoid organs later during infection. Additionally, in our study, low count of MDSC‐like cells in local lymph nodes at 6th dpi coincided with an increased pool of the cells in the blood and the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, during histotropic phase of infection, we saw increased numbers of CD11b+Gr‐1+ cells in peritoneal fluid. Peritoneal cavity was shown to be an important trafficking site for intestinal immunity; therefore, parasite‐induced cells could migrate through the peritoneum to other lymphoid organs later during infection. Additionally, in our study, low count of MDSC‐like cells in local lymph nodes at 6th dpi coincided with an increased pool of the cells in the blood and the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…110,111 On the other hand, we have recently shown that CMV infection in a murine model indeed impairs MDSC differentiation, thereby breaking transplantation tolerance mediated by MDSCs. 113 Furthermore, patients with chronic lung allograft dysfunction also has a lower level of G-MDSCs in the periphery. 112 In support of our findings, in an independent clinical study of lung transplant recipients, G-MDSCs are found to decrease in number with infection while expand in stable lung recipients.…”
Section: Myeloid Derived Suppressor Cells (Mdscs)mentioning
confidence: 99%
“…112 Acute CMV infection is found to inhibit G-MDSC expansion and impair the suppressive function of M-MDSCs. 113 However, there are also conflicting data reporting significant and persistent increase of M-MDSCs after bacterial infection in renal transplant recipients which contributes to postinfection immunodeficiency in these patients. 113 Furthermore, patients with chronic lung allograft dysfunction also has a lower level of G-MDSCs in the periphery.…”
Section: Myeloid Derived Suppressor Cells (Mdscs)mentioning
confidence: 99%
See 2 more Smart Citations